Phosphotransferase systems in Enterococcus faecalis OG1RF enhance anti-stress capacity in vitro and in vivo - Peng, Zhen; Miethke, Thomas (Research in microbiology, 2017)
Phosphotransferase systems are common and essential in bacteria, which are in charge of sugar transportation and phosphorylation. However, phosphotransferase systems were found in recent years to be associated with environmental stress factors. This study investigated the role of the mannose/fructose/sorbose phosphotransferase systems in Enterococcus faecalis OG1RF in adaption to harsh environments by construction of pts mutants. More than one mannose/fructose/sorbose phosphotransferase system was found in E. faecalis OG1RF, and the elimination of pts gene at different loci generated different after-effects corresponding to different ambiences. An in vitro study showed that the presence of intact phosphotransferase systems in E. faecalis OG1RF promoted resistance to hydrogen peroxide and acid and enhanced susceptibility to pediocin. In vivo study demonstrated that the presence of intact phosphotransferase systems induced more hazardous substances like superoxide dismutase (SOD) in Caenorhabditis elegans and enhanced bacterial infection and survival in macrophages J774A.1 and BMM. In addition, phosphotransferase systems regulated transcription of antioxidant and catabolite genes such as katA, gor, lysR, hypR, rex, hprK and tpx to different extents (−6.3- to 3.5-fold). It is therefore suggested that pts genes are regulatory factors promoting adaption of E. faecalis OG1RF to stressful conditions, thereby enhancing the possibility of bacterial survival and infectivity.